Risk perception and electronic cigarette use among nursing students at a public university in Mexico - Alcocer-Carranza, Jesús; Mata-Alonso, Francisco Daniel; Villareal-Sepúlveda, Mariana; Ruíz-Lázaro, Ana Karen Melissa; García-Alvarado, Omar; García-Pérez, Michelle Marisol (Universidad y Salud, 2025)
Introduction: Electronic cigarette consumption is an emerging public health problem, since this modality is attractive to users, a low-risk perception towards these devices predisposes to consumption, a risk group are nursing students. Objective: To determine the relationship between risk perception and electronic cigarette use among nursing students at a public university in Monterrey, Nuevo Leon, Mexico. Materials and methods: Descriptive and correlational cross-sectional study, using non-probabilistic convenience sampling, the sample consisted of 50 participants over 18 years of age who signed informed consent. Results: 60 % of the participants reported using electronic cigarettes at some time in their lives and 14 % in the last week. The age of onset of use was 18,4 years (SD = 1.7), women presented higher use in the last month (Tau-b = -0.26; p < 0.05). There was a significant negative relationship between risk perception and electronic cigarette consumption (rs = -0.13; p < 0.05). Conclusion: It is necessary to consider risk perception in future studies and in nursing education to prevent the use of electronic cigarettes.